Relationship between technical-tactical complexity in the training session and internal load in female basketball - Vallés Ortega, C.; Fernández-Ozcorta, E. J.; Fierro Suero, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The objective of this work was to analyze the rating scale load-Tactical Technical (Coque, 2009) Training and Its Relationship with internal load parameters. Currently, a planning model characterized by concern to improve the interpretation that the subject does what happens around them during the competition (Martin Steel, Seirul-lo Vargas, Lake Peñas, and Novoa Lalin arises, 2013), to modify the response and in turn, the drive scheme. The study involved the players formed Women’s League team Basketball Club Conquero, composed of 12 players, aged between 17 and 33 years (M = 21.91, SD = 4.81). Data were collected during the last two months of competition in February and March. Par obtain the data necessary the following scales of subjective assessment of the burden of technical and tactical training (Coque, 2009), perceived exertion (Borg, 1970; 1998; Borg & Kaijser,2006) and quality of recovery (Kentta & Hassmen, 1998) were used. The results showed that only the density of training is the only marker that could explain significantly (91.4%) perceived effort of the players. According to data from the perceived exertion, it could be used for monitoring training regarding technical and tactical complexity.